Preparation of hydrogel reinforced with bentonite by gamma irradiation for metal absorption - Uyen, Tran To; Anh, Trinh Thi Tu; Kume, Tamikazu; Vu, Cao Dong; Hiep, Nguyen Minh; Cuong, Le Xuan; Hoan, Nguyen Ngoc (Nuclear Science and Technology, 2020)
A natural-based sodium carboxymethyl cellulose (CMC) hydrogel reinforced with bentonite was prepared by using gamma irradiation technology. This is a novel hydrogel that uses natural polymer to absorb metal ions in wastewater. The influence of dose, concentration of CMC and bentonite on the sorption of hydrogels was investigated by atomic absorption spectrometry (AAS) method. According to the Langmuir isotherm model, the maximum adsorption capacities of CMC/bentonite hydrogel for Cu2+ and Pb2+ were 181.82 mg/g and 204.08 mg/g at room temperature, respectively. The pseudo-second-order model which describes the adsorption process of Cu2+ and Pb2+ was also studied